Aplikasi Fuzzy Logic Controller Untuk Pengukuran Suhu Tubuh Dan Detak Jantung Pada Anak Autism Spectrum Disorder Menggunakan Socially Assistive Robot - Prihatini, Ekawati; Irdayanti, Yeni; Rafly, Muhammad (Universitas Negeri Padang, 2024)
In the development of electronic technology, especially robots, they have played an important role in the medical field, including for overcoming the anxiety of autistic children and their health. This study used a SAR (Socially Assistive Robot) robot equipped with a heart rate and body temperature sensor to help reduce and indicate the anxiety and also health of autistic children. The MAX30100 sensor was used to detect heart rate, while the GY906 sensor was used to detect body temperature. The robot's response resembled a hand movement, which was a sign that a child's body temperature and heart rate were out of the ordinary (abnormal). The aim was to provide assistance to autistic children in dealing with anxiety and their health, making it easier for teachers to supervise autistic children, which could affect their emotional and social development. By using a fuzzy logic controller to analyze the response of MAX30100 sensors and GY906 sensors working optimally or not, with servo motor output.